2019
DOI: 10.1111/odi.13138
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐related leukocytosis predictive of recurrence and survival in patients with oral cavity squamous cell carcinoma

Abstract: Objective To evaluate the prognostic values of tumor‐related leukocytosis (TRL) as a reliable biomarker predictive of recurrence and survival after definitive surgery for oral cavity squamous cell carcinoma (OSCC). Materials and methods This retrospective study involved 322 patients who underwent tumor extirpation combined with neck dissection for treatment‐naïve OSCC between 2006 and 2014. Multivariate binary logistic regression analyses were used to analyze the relationship between TRL and pathological varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… 11 Leucocytosis has been linked to tumour recurrence and metastasis after surgery in oral squamous cell carcinoma and oropharyngeal cancer. 11 , 12 , 13 , 14 In another study by Jensen and colleagues demonstrated that pre-treated leucocytosis and neutrophilia were associated with a poor response to radiotherapy. 30 Several studies have indicated leucocytosis and neutrophilia to be predictors of poor OS and PFS in other cancers, such as anal, oesophageal and lung cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Leucocytosis has been linked to tumour recurrence and metastasis after surgery in oral squamous cell carcinoma and oropharyngeal cancer. 11 , 12 , 13 , 14 In another study by Jensen and colleagues demonstrated that pre-treated leucocytosis and neutrophilia were associated with a poor response to radiotherapy. 30 Several studies have indicated leucocytosis and neutrophilia to be predictors of poor OS and PFS in other cancers, such as anal, oesophageal and lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Numerous studies have also related leucocytosis and neutrophilia to the outcome of HNSCC after evaluating different therapeutic strategies. 11 , 12 , 13 , 14 This study aimed to investigate each of the aforementioned parameters and their relationships with the cohort's response to the treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of TRL, a paraneoplastic syndrome, has been reported in 10%–20% of cancer patients and is associated with a poor prognosis. It has been observed that TRL does not respond well to radiotherapy or chemotherapy, leading to poor survival outcomes ( 56 , 57 ). The general characteristics and treatments are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%